Omecamtiv mecarbil for the management of heart failure: a meta-analysis of randomized controlled trials. (3rd October 2022) - Silva, M M C A; Fernandes, A; Hurtado, V; Fernandes, G; Cardoso, R; Andersson, C
Abstract: Background: Omecamtiv mecarbil (OM) is a selective cardiac myosin activator that promotes contractility in patients with Heart Failure with Reduced Ejection Fraction (HFrEF). We aimed to study the clinical outcomes of OM in this population. Methods: PubMed, Cochrane CENTRAL Registry of Controlled Trials, and ClinicalTrials.gov were searched for randomized controlled trials (RCTs) that compared OM with placebo for the management of HFrEF. Efficacy and safety data were summarized with odds ratios (OR) and a 95% confidence interval (CI) using a fixed-effect model predicting low heterogeneity between studies. Results: Four RCTs were included, totalizing 9, 364 patients, 4, 779 treated with OM and 4, 585 with placebo. Mean age ranged from 63–66 years, 15–22% female, ejection fraction 26–29%, ischemic etiology 53–66%. Length of follow up ranged from 1 to 21 months. There was no difference in the outcomes all cause death (OR 0.99, 95% CI 0.9–1.1, p=0.91), cardiovascular death (OR 1.01, 95% CI 0.91–1.12, p=0.87) and heart failure events or hospitalizations (OR 0.96, 95% CI 0.87–1.05, p=0.35), Figure. Conclusion: In a meta-analysis of 4 RCTs, OM showed no difference compared with placebo in the risk of all-cause death, cardiovascular death, or heart failure events among patients with HFrEF. Funding Acknowledgement: Type of funding sources: None.